2002
DOI: 10.1046/j.1471-4159.2002.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin‐dependent kinase II phosphorylation of the GABAA receptor α1 subunit modulates benzodiazepine binding

Abstract: c-Aminobutyric acid (GABA) is the primary neurotransmitter that is responsible for the fast inhibitory synaptic transmission in the central nervous system. A major post-translational mechanism that can rapidly regulate GABA A R function is receptor phosphorylation. This study was designed to test the effect of endogenous calcium and calmodulin-dependent kinase II (CaM kinase II) activation on both allosteric modulator binding and GABA A receptor subunit phosphorylation. Endogenous CaM kinase II activity was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…Our findings are consistent with other behavioral studies that also show that antagonism of CaMKII within the BLA will block the acquisition of aversive behaviors (Tan and Liang, 1997) but not the expression of the behavior (Malinow et al, 1989). Paradoxically, acute CaMKII activation has been reported to enhance GABA A receptormediated transmission (Churn et al, 2002;Kawaguchi and Hirano, 2002). However, a preferential downregulation of GABA A receptors has been reported in the neocortex after withdrawal from periods of elevated GABA A receptor activation, resulting in hyperexcitability and seizure activity (S. S. Casasola et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with other behavioral studies that also show that antagonism of CaMKII within the BLA will block the acquisition of aversive behaviors (Tan and Liang, 1997) but not the expression of the behavior (Malinow et al, 1989). Paradoxically, acute CaMKII activation has been reported to enhance GABA A receptormediated transmission (Churn et al, 2002;Kawaguchi and Hirano, 2002). However, a preferential downregulation of GABA A receptors has been reported in the neocortex after withdrawal from periods of elevated GABA A receptor activation, resulting in hyperexcitability and seizure activity (S. S. Casasola et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…We next investigated the involvement of CaMKII as follows: (1) it is activated by Ca 2ϩ , (2) it is known to phosphorylate the GABA A R (Churn et al, 2002), (3) infusion of Ca 2ϩ -CaM has been shown to increase GABA A R currents in CA1 pyramidal neurons (Wei et al, 2004), and (4) Ca 2ϩ -CaM-dependent enhancement is blocked by addition of an autoinhibitory form of CaMKII (Wei et al, 2004). When we inhibited CaMKII in cultured neu- , intensity of synaptic, GAD-65-overlapping GABA A R puncta (black bar), as well as the overall number of GABA A R puncta per 10 m length of dendrite (dark gray bar) (n ϭ 5).…”
Section: Chem-ltd Nmda Receptor Activation Increases Surface Gaba a Rmentioning
confidence: 99%
“…Diazepam may thus limit the neuronal responsiveness to changes in intracellular Ca 2+ levels. Several studies have pointed to the presence of consensus sites for CaMKII phosphorylation of the GABA A receptor in c2L, c2S and b subunits (Machu et al 1993;McDonald and Moss 1994), and phosphorylation of the a1 subunit has been demonstrated to lead to an increase in benzodiazepine binding (Churn et al 2002). CaMKIIa has also been shown to positively modulate GABA-induced Cl -currents (Wang et al 1995).…”
Section: Change In Calcium Responsivenessmentioning
confidence: 99%